EFEKTIFITAS PENGGUNAAN MEDIA CUBARITME UNTUK MENINGKATKAN KEMAMPUAN PENJUMLAHAN DERET KE BAWAH DENGAN TEKNIK MENYIMPAN BAGI ANAK TUNAGRAHITA RINGAN - Silvia Wirdamaini; Kasiyati Kasiyati; Fatmawati Fatmawati (Universitas Negeri Padang, 2013)
This research of background overshadow by problems which is researcher find in SDLBN 20 Pondok Duo Town of Pariaman,a child of intelegance below natural light of internal issue quantifying of compile downwards with technique of hiding. Pursuant to the mentioned hence this research aim to prove efektifity usage of media of cubaritme to increase quantifying of compile downwards with technique of hiding to child of intelegance below of class DIII /C in SDLBN 20 Pondok Duo Town of Pariaman. This research use approach of Single Subject Research, designed by A-B-A and technique analyse its data use visual analysis of graph. Research Subjek is a child of intelegance below of class DIII /C, which a child in errand finish problem quantifying of compile downwards with technique of hiding at answer sheet. Many problem which in giving ten item each time meeting, and measurement of its variable by using percentage. Result of this research indicate that media of Cubaritme effective in improving quantifying of compile downwards with technique of hiding to a child intelegance below of class DIII/C SDLBN 20 Koto Duo Town of Pariaman. This in proving with result of intervention conducted (A1) the seven of perception times rill, percentage of ability of quantifying of compile downwards with technique of hiding lay in to span 0%, and 10%. Both, intervention (B) by using media of Cubaritme perception conducted by counted ten times, percentage of ability of quantifying of compile downwards with technique of hiding at spanning 20% until 100%. Baseline after shall not longger use media of Cubaritme (A2) conducted by the five of perception times rill, got by result of ability of a child in quantifying of compile downwards with technique of hiding lay in to span 70% until 100%. Pursuant to result of the research can be concluded by media of Cubaritme effective in improving quantifying of compile downwards with technique of hiding. Researcher suggest to researcher and teacher here in after so that to be can use media of cubaritme to increase quantifying of compile downwards with technique of hiding a child.